An Introduction To Ethics - Deigh, John (New York, NY : Cambridge University Press, 2024.)
A clear, comprehensive presentation of the most important theories of ethics in Western philosophy, including extensive coverage of John Rawls's theory. Students will find this book to be a helpful guide to how philosophical inquiry is undertaken as well as to what the major theories of ethics hold